Application of Maqasid Al-Shariah in Islamic Economics and Finance as the Development of Products of Islamic Value - Fadilla Syahriani; Fini Fajri Mulyani; Fismanelly Fismanelly; Sarah Afifah; Alex Medani (Hakamain: Journal of Sharia and Law Studies, 2023)
This research aims to analyze the application of Maqasid Al-Shariah in Islamic Economics and Finance for developing products with Islamic values. Maqasid Al-Shariah, which includes the primary objectives of Islamic law protection of religion, life, intellect, lineage, and property is the focus to ensure financial products comply with Shariah law and benefit the Muslim community.A qualitative descriptive analysis method is used to illustrate how Maqasid Al-Shariah is implemented in Islamic economics and finance. Data collection involves comprehensive literature reviews, in-depth interviews with Islamic economic experts, and documentation of Shariah-compliant financial products. The literature review provides a theoretical foundation, while interviews and documentation offer practical insights into Maqasid Al-Shariah's real-world applications.The findings indicate that Maqasid Al-Shariah plays a crucial role in guiding the development of Islamic financial products that reflect Islamic values and meet the Muslim community's needs. In-depth analysis of financial products, such as savings, investments, and Shariah-compliant financing, shows how Maqasid Al-Shariah underpins their development. For instance, savings and investment products based on Maqasid Al-Shariah ensure halal funds, fair profit distribution, and risk protection.The practical implications of this research are significant for Islamic financial industry practitioners. Understanding Maqasid Al-Shariah's application helps them design and develop products that comply with Shariah principles and benefit the Muslim population. These products are expected to comprehensively meet the financial needs of the Muslim community, including protection against economic uncertainties, sustainable wealth management, and contributions to overall social welfare.